(untitled) (Applied Biological Research, 2015)
The present study was aimed to assess the protective effect of Moringa oleifera fruits extract against sodium fluoride induced down-regulation of collagen-1 gene in tibia bone of rats. Twenty four albino rats were randomly assigned to four groups. The 1st group served as control and received only tap water. The 2nd group received sodium fluoride (200 ppm) through drinking water. The 3rd group received extract of M. oleifera alone and 4th group received M. oleifera extract alongwith fluorinated drinking water, daily by gavage for 8 weeks. Significant decrease in the expression of collagen-1 gene in tibia bone was noted in fluoride treated rats. of M. oleifera fruits extract during exposure to fluoride up-regulated the expression of collagen-1 gene in tibia bone as compared to untreated fluoride exposed rats. It is concluded that daily oral administration of M. oleifera fruit extract has positive influence on the expression of collagen-1 gene in bones of fluoride intoxicated rats.